BKLYN fashion academy: a case study of a public library program supporting fashion entrepreneurs. Issue 1 (3rd April 2019) - Tully, Tim
Abstract: This case study presents the planning and implementation of a public library program that supported aspiring fashion entrepreneurs. The program participants developed miniature collections through a combination of courses and access to materials and equipment, and they showcased their designs in a culminating runway show. The library partnered with outside organizations to connect these individuals with the library resources, mentorship, and technical assistance that would help them create their own brands and, ultimately, market and sell their own products.